Actual knowledge and expansion of the distribution of the Tricorythopsis rondoniensis (Ephemeroptera, Leptohyphidae). (2016)
With this work, the known distribution of Tricorythopsis rondoniensis in Colombia is expanded, with the first record of this species for the Amazonas and Guaviare Colombian departments. Additionally, the known distribution of T. rondoniensis expands in the department of Meta, with a new record for the Municipality of San Juan de Arama, the closest to Andean region for the genus. These findings extend the records of this species in Colombia and corroborate the proposed distribution for the genus Tricorythopsis.